Political Poster in the Croatian Iconosphere - Darasz, Zdzisław (Poznańskie Studia Slawistyczne, 2020)
The titular problem of Croatian political poster, regarded as an art of margins, is treated by the author, according to the order of chapters, in four main aspects: historical, aesthetic, socio-political, and cultural one. The development of poster art, correlated with national history in 19th and 20th century Croatia, is presented in the chapter “In the vapour of history”. In the next chapters some particular sections of the searching field are described. These sections are as follows: technique of montage of the pictures, modern iconoclastic practices, chaos vs. order, and the place (“From margin to centre”).